Coverage of climate change: perceptions of information sources and journalists (Comunicação & Inovação, 2017)
The article discusses the coverage of climate change through the perceptions of the sources of information and journalists of Gazeta do Povo. This paper is about the news production process of a theme that encompasses multiple levels, uncertainties and non-tangible risks for the population. It presents a content analysis from interviews with those involved in this production. The results show that the need for a relationship between local and global, and a preventive approach are recognized, although the journalistic logic and generalist profile of journalists induce them to write more specific news.
Keywords: Journalists. Information sources. Climate change.